DESENVOLVIMENTO DE PLANILHA ELETRÔNICA PARA CÁLCULO DO ISOLAMENTO ACÚSTICO POR VIA ÁEREA CONSIDERANDO A ENERGIA LATERAL - Zara, Rafaela Benan; Soares, Paulo Fernando (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
With increasing requirements regarding the performance of a building, it becomes increasingly necessary to use methods that can predict the reduction of the noise level inside a building. These methods are, in general, complex and require a variety of information. Thus, this work aims to develop a spreadsheet for calculation of acoustic insulation by air between adjacent environments and facades in the design phase. The spreadsheet was prepared in Microsoft Excel based on ANIT calculation method. The programming was performed using the Visual Basic for Application, with several options of applied materials, types of joints and shape of the facade. For spreadsheet validation, a case study was carried out, comparing the simulation results with the Noise Insulation Software (NIS) and the field measurement. All the results presented close values, demonstrating the spreadsheet efficiency. However, it is still necessary to study new cases to verify the scope of it.